2001
DOI: 10.1042/cs1000239
|View full text |Cite
|
Sign up to set email alerts
|

A simple, highly sensitive and improved method for the measurement of bleomycin-detectable iron: the ‘catalytic iron index’ and its value in the assessment of iron status in haemochromatosis

Abstract: In the presence of ferrous ions (Fe(2+)), the anti-tumour agent bleomycin will induce DNA degradation. Degradation of DNA into substances detectable by the thiobarbituric acid test has been used previously for the detection of iron in a form that is capable of catalysing the formation of the potentially harmful hydroxyl free radical. In the present paper, we describe the application of the ethidium-binding assay of DNA damage to the measurement of bleomycin-detectable iron, comparing its performance with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…To ascertain whether Ent could quench the reactivity of LIP, we modified the bleomycin-based LIP detection assay that was originally developed to quantify LIP in biological samples (19). In our modified assay system, we instead prepared a series of samples with known concentrations of labile iron and tested whether Ent could quench their detection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ascertain whether Ent could quench the reactivity of LIP, we modified the bleomycin-based LIP detection assay that was originally developed to quantify LIP in biological samples (19). In our modified assay system, we instead prepared a series of samples with known concentrations of labile iron and tested whether Ent could quench their detection.…”
Section: Resultsmentioning
confidence: 99%
“…The assay was performed as outlined by Burkitt et al (19) with modifications described previously (20). In principle, ascorbic acid converts Fe +3 into Fe +2 , which in combination with bleomycin, causes DNA breaks.…”
Section: Methodsmentioning
confidence: 99%
“…The assay has been shown to be unresponsive to iron bound to storage, transport and other proteins, being negative for the presence of free iron in plasma or serum from healthy individuals [98]. In contrast, the assay has confirmed the presence of free iron in individuals with iron overload (genetic haemochromatosis) [30,99] and in certain pathological situations, such as the rheumatoid joint [91,98] and during cancer chemotherapy [100,101]. Using NMR spectroscopy, Grootveld and colleagues have demonstrated that the free iron in plasma and serum from haemochromatosis patients is associated with citrate.…”
Section: Biological Aspects 3·1mentioning
confidence: 92%
“…Various methods have been developed to detect 'free' iron (assumed to be complexed to low molecular weight molecules, such as citrate and the adenine nucleotides), but, invariably, these involve the use of powerful iron chelating agents that, it can be argued, may mobilise iron from sites where it would not otherwise be capable of catalysing • OH generation [91][92][93][94][95][96]. Perhaps the most successful of these assays has been the so-called bleomycin assay, which relies on the ability of the anti-tumour agent bleomycin to degrade DNA in the presence of iron [30,91,97]. The assay has been shown to be unresponsive to iron bound to storage, transport and other proteins, being negative for the presence of free iron in plasma or serum from healthy individuals [98].…”
Section: Biological Aspects 3·1mentioning
confidence: 99%
“…The procedure followed for the BDI assay was based on previous published methods [4,7,8]. Briefly, for each serum sample or standard, the following reagents were combined in polypropylene tubes in the following order: 100 lL 1 M trishydroxymethylaminomethane buffer, 250 lL 1 mg mL )1 deoxyribonucleic acid solution, 25 lL 1AE5 units mL )1 bleomycin solution, 25 lL serum blank, serum containing sample or standard, 50 lL 50 mM magnesium chloride solution and 50 lL 8 mM ascorbic acid solution.…”
Section: Bdi Assaymentioning
confidence: 99%